Exploring the Roles of Agents and Multi-Agent in Improving Mobile Ad Hoc Networks - Jubair M.A.; Alabdullah A.I.M.; Mostafa S.A.; Mustapha A.; Hassan M.H.; Gunasekaran S.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Heterogeneous networks; Mobile ad hoc networks; Mobile agents; Mobile telecommunication systems; Network architecture; Adaptive networks; Agent systems; Dynamic environments; Mobile ad-hoc networks; Mobile environments; Multi agent; Multi-hops; Robust network; Routing services; Self-organising; Multi agent systems